The blizzard challenge in the wild you're stronger together - Grylls, Bear; McCann, Emma (London, England, Bear Grylls, 2019)
Olly isn't enjoying activity camp. Why should he bother building a shelter or foraging for food with his teammates - he'd rather be at home in the warm and dry, where the sofa and the video games are. But then Olly gets given a compass with a mysterious fifth direction. When he follows it, he's magically transported to a high mountain range where he meets survival expert Bear Grylls. With his help, Olly must learn to survive in sub-zero temperatures, including what to do if the ice cracks when you're crossing a frozen lake, or a blizzard sets in ... But can his adventure with Bear Grylls change Olly's mind about teamwork and perseverance? And who will Olly give the compass to next?